The competitiveness and performance of the Zimbabwe poultry industry - Zengeni, Tatenda (My University, 2015)
This dissertation analyzes the competitiveness and performance of the Zimbabwean poultry industry in the context of trade liberalization, given that both poultry output and the main inputs (animal feed and breeding stock) are tradable. Poultry is an important product as the main source of protein for consumers. It also has strong links to agriculture through the production of animal feed. Despite the rise in chicken demand over the years as a cheap source of protein, the poultry industry in Zimbabwe still faces a number of challenges which the government claims include stiff competition from cheap imports, rising input costs of maize and soya meal and illegal imports being sold at sub-economic prices. This study evaluates these factors and the impact of changing trade protection. The methodology used in this study is both qualitative and quantitative. An analysis is done on trade tariffs particularly focusing on their effect to the poultry industry. Disaggregated trade and tariff data was used to analyze the evolution of tariff regime in the industry and to calculate the effective rate of protection of the poultry sector. A value chain approach was used to understand the linkages and interests that exist in this industry. The poultry industry has been affected by imports starting 2007 and has not been exporting since then as the industry struggled to compete on the domestic market. The study showed that the effective rate of protection calculation is complicated by the different trade regimes which currently exist. If the main international competition is from South Africa then the existence of the bi-lateral agreement between Zimbabwe and South Africa means that the poultry sector has not been protected. The study has shown that the breeding subsector is characterized by a duopoly since there are only two breeding firms in Zimbabwe and the comparison carried out revealed that Zimbabwean prices of day old chicks are above those of comparable countries in the region such as South Africa. The study shows that prices for GMO maize used in South Africa are substantially cheaper than Zimbabwean prices, thereby making Zimbabwean producers uncompetitive. The study recommends policies that attract investment in the breeding sub-sector of the value chain to increase competition, a review of GMO maize policy and reducing tariffs of imported raw materials used in the poultry industry.
Thesis M.Com. (Development Theory and Policy) -- University of the Witwatersrand, Faculty of Commerce, 2014
Keywords: Poultry; GMO maize; Competitiveness; Zimbabwe; Effective rate of protection